Magnetization states and magnetization processes in nanostructures: From a single layer to multilayers (Phys. Status Solidi A 5∕2014). Issue 5 (May 2014) - Maziewski, Andrzej; Fassbender, Jürgen; Kisielewski, Jan; Kisielewski, Marek; Kurant, Zbigniew; Mazalski, Piotr; Stobiecki, Feliks; Stupakiewicz, Andrzej; Sveklo, Iosif; Tekielak, Maria; Wawro, Andrzej; Zablotskii, Vitalii
<x xml:space="preserve">Abstract</x> Magnetization distributions in ultrathin magnetic either single layers or multilayers might be manipulated by: the thickness of the magnetic layers, the thickness of the nonmagnetic either cap/buffer or spacer layers, magnetic anisotropy and geometrical confinement of the system. Such layers are very promising candidate as a material for e.g. high‐density storage media. But one of the challenges is to find a method which allows to perform a precise and controlled manipulation of the properties. Very recently it has been discovered in ultrathin magnetic films that both the magnetization distribution and the critical thickness of a magnetization reorientation phase transition between perpendicular and in‐plane states, can be also controlled by the post‐growth treatments, e.g. by either ion or light irradiation. The cover image shows the example of a two‐dimension diagram of the polar Kerr rotation angle remanence versus ultrathin Co thickness and Ga+ ion fluence. The non‐irradiated region is marked as the "reference". Regions with zero remanence correspond to: (i) in‐plane magnetization orientation (blue area) and (ii) superparamagnetic properties (magenta area). The regions with enhanced magneto‐optical effects correspond to out‐of‐plane magnetization states. The irradiation induces two branches of out‐of‐plane magnetization states. Magnetization distributions in single ultrathin layer and multilayers have been studied both experimentally and theoretically. The huge changes of these distributions, driven by the nanostructure geometry or magnetic field, are discussed in the Feature Article by Maziewski et al. (pp. 1005–1018). The irradiation‐induced effects open novel routes for both tailoring thin‐film magnetic and magneto‐optical properties and patterning of magnetic nanostructures. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>